PERBANDINGAN PENGARUH AIR REBUSAN DAUN SALAM (SYZYGIUM POLYANTHUM) DAN DAUN KELOR (MORINGA OLEIFERA) TERHADAP KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2: COMPARISON THE EFFECTS OF BAY LEAF (SYZYGIUM POLYANTHUM) AND MORINGA LEAF (MORINGA OLEIFERA) ON BLOOD GLUCOSE LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Agung Budi Prayoga; Herdy Juniawan; Novia Susanti (WELL BEING, 2025)
Type 2 diabetes mellitus is a progressive metabolic condition associated with insulin resistance and hyperglycemia. Achieving adequate glycemic control remains a key strategy in reducing the risk of diabetic complications. This research investigated the effectiveness of bay leaf (Syzygium polyanthum) and moringa leaf (Moringa oleifera) decoctions as complementary approaches to manage blood glucose levels among type 2 diabetes patients in Manunggal Village, under the supervision of UPTD Puskesmas Batulicin I. The study adopted a quasi-experimental design employing a two-group pretest–posttest method. A total of 20 female respondents aged 41–60 years were purposively selected and evenly allocated to two intervention groups: bay leaf decoction and moringa leaf decoction. Participants consumed 200 ml of decoction twice daily for seven days. The findings revealed that while bay leaf decoction reduced blood glucose to a moderate category (mean post-test 208.6 mg/dL), moringa leaf decoction produced a significantly greater effect, with a mean post-test of 165.3 mg/dL (p = 0.000,